Kompetensi dan Motivasi Sebagai Variabel yang Mempengaruhi Kinerja Karyawan RSUD. Sultan Fatah Demak - Syamsul Hadi; Andhi Supriyadi (STEKOM PRESS, 2021)
This research was conducted to be able to find out the influence of competency and motivation variables on the performance of RSUD Sultan Fatah Demak employees. And it can also be known which variables have the highest influence on the performance of RSUD Sultan Fatah Demak employees. The method used in this study is a quantitative method, using statistical methods using questionnaires given to respondents. Respondents will answer by choosing numbers from existing statements about the influence of Competence and Motivation on the Performance of RSUD Sultan Fatah Demak employees. This research uses the study of library methods, questionnaire methods which are then processed with SPSS for windows 25.0. The sample of respondents in the study was 78 people. From the results of research both variables can be known motivation is shown as a variable that has the highest influence on employee performance in RSUD. Sultan Fatah with more value of 0.511 to employee performance